2019
DOI: 10.1002/ejoc.201900143
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light Enables Aerobic Iodine Catalyzed Glycosylation

Abstract: A versatile protocol for light induced catalytic activation of thioglycosides using iodine as an inexpensive and readily available photocatalyst was developed. Oxygen serves as a green and cost‐efficient terminal oxidant and irradiation is performed with a common household LED‐bulb. The scope of this glycosylation protocol was investigated in the synthesis of O‐glycosides with yields up to 95 %.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 52 publications
2
14
0
Order By: Relevance
“…However, when the reaction time was further reduced to 2 hours, only 70% yield was obtained and 1 a was not completely consumed. The testing of different solvents could not further improve the reaction outcome ( Table 1, entries [12][13][14][15][16]. Control experiments demonstrated the essential role of the I 2 and visible light in the reaction (Table 1, entries 17 and 18).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the reaction time was further reduced to 2 hours, only 70% yield was obtained and 1 a was not completely consumed. The testing of different solvents could not further improve the reaction outcome ( Table 1, entries [12][13][14][15][16]. Control experiments demonstrated the essential role of the I 2 and visible light in the reaction (Table 1, entries 17 and 18).…”
Section: Resultsmentioning
confidence: 99%
“…Following our continuous interest in the synthesis of 1,2,3-triazoles via CÀ H functionalization [11] as well as visible-lightmediated synthesis, [12] we would like to report herein a mild and efficient construction of highly functionalized 1,2,3-triazolo[1,5-a]quinazolin-5(4H)-ones through visible-light promoted intramolecular azole CÀ H bond amination of easily available 2-(1,2,3-triazol-1-yl) benzamides (Scheme 1), in which catalytic amount elementary I 2 was used as a simple and metal-free initiator. [13]…”
Section: Introductionmentioning
confidence: 99%
“…In this case, energy transfer originates from ruthenium to oxygen and not from iodine. Our lab recently investigated the cleavage of thioglycosides with iodine photocatalysis in combination with oxygen as the terminal oxidant . Thioglycosides were activated by catalytic amounts of iodine to release glycosyl cation intermediates which reacted with alcohols to produce various O ‐glycosides (Scheme , c).…”
Section: Methodsmentioning
confidence: 99%
“…Earlier last year, we have been working on an iodine‐catalyzed glycosylation reaction with thioglycosides as glycosyl donors. In this report, we demonstrated that molecular iodine acts as a potent photocatalyst for C–S bond activation and singlet oxygen generation . As C–S‐bonds are part of many interesting organic molecules, our initial work prompted us to investigate further applications for the iodine/oxygen dual photosystem.…”
Section: What Prompted You To Investigate This Topic?mentioning
confidence: 96%